2016
DOI: 10.1002/14651858.cd011119.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of patient reported outcome measures (PROMs) for improving treatment of common mental health disorders in adults

Abstract: We found insufficient evidence to support the use of routine outcome monitoring using PROMs in the treatment of CMHDs, in terms of improving patient outcomes or in improving management. The findings are subject to considerable uncertainty however, due to the high risk of bias in the large majority of trials meeting the inclusion criteria, which means further research is very likely to have an important impact on the estimate of effect and is likely to change the estimate. More research of better quality is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
167
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 104 publications
9
167
2
10
Order By: Relevance
“…The results of this study are at odds with the published studies in CFT showing that ROM is associated with better outcomes compared to TAU (e.g., Anker et al, 2009;Reese et al, 2010). We find, however, our results in agreement with the Cochrane report (Kendrick et al, 2016) that did not find evidence for a difference in outcome (psychiatric Higher is better, meaning an increase in score from t1 to t2 is an improvement. The other instruments show that lower is better.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The results of this study are at odds with the published studies in CFT showing that ROM is associated with better outcomes compared to TAU (e.g., Anker et al, 2009;Reese et al, 2010). We find, however, our results in agreement with the Cochrane report (Kendrick et al, 2016) that did not find evidence for a difference in outcome (psychiatric Higher is better, meaning an increase in score from t1 to t2 is an improvement. The other instruments show that lower is better.…”
Section: Discussioncontrasting
confidence: 83%
“…However, not all findings have been in favor of ROM. A Cochrane report, which included 17 studies involving 8,787 adult participants treated for mental health disorders, found that ROM and TAU conditions did not significantly differ (Kendrick et al, 2016). More specifically, Janse deJong, Van Dijk, Hutschemaekers, and Verbraak (2017) found that ROM was not more beneficial for 1,006 outpatients than TAU in general with the exception of those suffering from mood disorders who benefited more from ROM.…”
Section: Introductionmentioning
confidence: 99%
“…Despite our inconclusive findings, both patient dissatisfaction and procedural issues with the current process of using PROs suggest the need to explore novel technologies, such as PRO/CFS. These systems have been proven effective in symptom management in patients with psychiatric diseases (1,33), and may be useful for patients seeking treatment for obesity, given their high prevalence of psychological issues (22). Such a system collects patientreported outcomes before, during and after treatment, and is easily implemented using an electronic device, such as a tablet, that displays visual data for both patient and healthcare provider (5).…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews (33,34) were assessed as being of good quality due to a comprehensive literature search in relevant databases, contact with experts in the field, and searches for grey literature. In addition, two or more authors had screened references, decided upon inclusion, and analysed the data.…”
Section: Quality Of Included Reviewsmentioning
confidence: 99%
“…Se ha recopilado más información sobre el impacto de la retroalimentación en los profesionales de la salud mental acerca de los resultados y el uso de herramientas de resolución de problemas (por ejemplo, Kendrick et al, 2016;Krägeloh, Czuba, Billington, Kersten y Siegert, 2015;Shimokawa, Lambert, y Smart, 2010). Si bien la retroalimentación no parece mostrar un efecto beneficioso adicional en los resultados para los pacientes que ya están respondiendo bien a la terapia (es decir, pacientes encarrilados), los estudios podrían encontrar efectos beneficiosos en los resultados para los pacientes que no muestran un buen progreso o presentan un alto riesgo de deterioro (los denominados casos "mal encarrilados", por ejemplo, Crits-Christoph et al, 2012;Gondek, Edbrooke-Childs, Fink, Deighton y Wolpert, 2016;Harmon et al, 2007;Probst et al , 2013).…”
unclassified